Cu2O-loaded ZnZrOx composite metal oxide reverse-phase catalyst for preparing methanol based on carbon dioxide hydrogenation

Through the preparation of Cu2O-supported ZnZrOx composite metal oxide reverse phase catalyst, the problems of poor stability and low hydrogenation performance in the process of CO2 hydrogenation and methanol production were solved, and a catalytic effect with high activity and high selectivity was achieved.

CN119500153AActive Publication Date: 2025-02-25BEIJING UNIV OF TECH

Patent Information

Application Number
CN202411628061.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-02-25
Estimated Expiration
2044-11-14

AI Technical Summary

Technical Problem

The existing Cu-based catalysts have problems such as poor stability, sintering and aggregation of active sites, and low hydrogenation performance in the process of hydrogenation of CO2, making it difficult to effectively catalyze the reaction.

Method used

Cu2O-supported ZnZrOx composite metal oxide reverse phase catalyst was prepared by liquid phase reduction method to regulate the surface oxide modification and metal support size of the catalyst to improve the activity and selectivity of the catalytic reaction.

Benefits of technology

It significantly improves the stability of the catalyst and the selectivity of methanol, improves the activity of CO2 hydrogenation reaction, and solves the problems of low stability and hydrogenation performance of traditional catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500153A_ABST
    Figure CN119500153A_ABST
Patent Text Reader

Abstract

The invention relates to a Cu2O loaded ZnZrOx composite metal oxide reverse-phase catalyst for preparing methanol based on carbon dioxide hydrogenation, and belongs to the field of carbon neutralization. The invention provides a Cu2O-loaded ZnZrOx composite metal oxide reverse catalyst with high thermal stability, strong anti-sintering capability and excellent hydrogenation activity due to the problems of poor stability, sintering agglomeration of active sites, low hydrogenation performance and the like existing in the current catalyst, which has important research value in preparation of methanol by hydrogenation of carbon dioxide under the background of double carbon. The invention provides the Cu2O-loaded ZnZrOx composite metal oxide reverse catalyst. The Cu2O-loaded ZnZrOx composite metal oxide reverse catalyst has the advantages of high thermal stability, strong anti-sintering capability and excellent hydrogenation activity. The reverse catalyst has good methanol selectivity and stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of carbon neutrality, and specifically relates to a Cu2O-loaded ZnZrO x The composite metal oxide reverse catalyst is used for the hydrogenation of carbon dioxide to methanol. Background Art

[0002] With the continuous development of the world's industry, global greenhouse gas emissions continue to increase, the greenhouse effect is becoming more serious, and climate change has brought very severe challenges to our lives. According to research statistics, CO2 is the main gas causing the greenhouse effect, accounting for more than 70% of global greenhouse gases, leading to a series of ecological and environmental problems and energy crises such as sea level rise, glacier melting, and ocean acidification. The synthesis of methanol using CO2 as raw material has opened up a new way for the effective utilization of carbon resources.

[0003] Cu-based catalysts are the most widely used of all types of methanol catalysts, with advantages such as large specific surface area and high dispersion. However, studies have shown that Cu-based catalysts have many problems during the reaction, such as poor stability, sintering and agglomeration of active sites, and low hydrogenation performance, and do not have the ability to effectively catalyze CO2 hydrogenation to methanol. However, the introduction of oxides such as ZnO and ZrO2 can effectively improve the dispersion of Cu and the stability of the catalyst, forming a Cu-Zn synergistic effect.

[0004] Traditional supported oxide catalysts usually load metals on the surface of oxides, which have large surface energy and unstable structure, making it difficult to obtain a single valence state for active site research. Inverse catalysts disperse oxide nanoparticles on the metal surface, and the electronic and chemical properties of the oxides change accordingly with the particle size and the interaction between the oxide and the metal support. The metal exists in the form of a bulk support, providing metal sites. Therefore, the oxide sites, metal sites, and metal-oxide interface sites in the reverse catalyst system can simultaneously adsorb and activate different reaction substrate molecules and promote the further transformation of related intermediate species.

[0005] The present invention selects a copper-containing compound as a precursor, selects sodium citrate as a reducing agent, and adopts sodium hydroxide as a precipitating agent to prepare a Cu2O-loaded ZnZrO by a liquid phase reduction method. xThe composite metal oxide reverse catalyst of the present invention. The innovation of the catalyst in structure and catalytic reaction pathway has formed excellent catalytic performance in CO2 hydrogenation reaction. By regulating the surface oxide modification of the catalyst, the size of the metal carrier, etc., the activity of the catalytic reaction, the selectivity of methanol and the stability of the catalyst are improved. At the same time, these innovations not only improve the performance of the catalyst, but also provide a new way to achieve green energy and chemical preparation. By converting CO2 into a high-value-added liquid methanol resource, it is expected to effectively solve the dual problems of environment and energy. Summary of the invention

[0006] The present invention aims to solve the problems of poor stability of current catalysts, sintering and agglomeration of active sites, and low hydrogenation performance, and provides a Cu2O-loaded ZnZrO catalyst with high stability and reduction resistance. x The composite metal oxide reverse phase catalyst has good methanol selectivity and stability.

[0007] In a first aspect, an embodiment of the present invention provides a Cu2O-loaded ZnZrO x The composite metal oxide reverse phase catalyst is applied to CO2 hydrogenation to produce methanol, and is characterized by comprising:

[0008] Containing Cu2O support and ZnZrO x Oxide reverse catalyst, x is 1-3.

[0009] Optionally, the powder size of the Cu2O carrier is 10 to 2000 nm, and the ZnZrO x The powder size of the oxide is 1 to 100 nm.

[0010] In a second aspect, an embodiment of the present invention provides a Cu2O-loaded ZnZrO x The preparation method of the composite metal oxide reverse phase catalyst is characterized in that a fixed bed reactor is used, a mixed gas with a molar ratio of CO2 / H2 / N2=1 / 1.0~5.0 / 0.5~5 is introduced, the flow rate is controlled at 10~150mL / min, the reaction pressure is maintained at 0.5~5MPa, the reaction temperature is set at 180~300℃, and a gas chromatograph is used for online detection and calculation to obtain the CO2 conversion rate and methanol selectivity. The preparation method specifically comprises the following steps:

[0011] (1) Contains Cu 2+The precursor, the reducing agent, the 4.8M NaOH solution and the ultrapure water are mixed uniformly in a mass ratio of 1-15:10-25:10-25:500-2500, the reaction temperature is set to 50-150°C, and the reaction is stirred at a speed of 100-1000 rpm for 0.5-25 hours. Subsequently, 0.1-15g of ascorbic acid is added, and the reaction is stirred at a speed of 100-1000 rpm for 0.5-30 hours. After the product is cooled to room temperature, it is alternately washed with ultrapure water and anhydrous ethanol and centrifuged. It is dried in a vacuum drying oven at 40-100°C for 6-72 hours to obtain the Cu2O material.

[0012] (2) Cu2O and Zn obtained in step (1) above 2+ Precursor, Zr 4+ The precursor and ultrapure water are mixed evenly in a mass ratio of 1.5-15:0.1-3:0.1-5:1.5-15, the reaction temperature is set to 50-250°C, and the reaction is stirred at a speed of 100-1000 rpm for 0.5-30 hours. Dry in a vacuum drying oven at 40-100°C for 6-72 hours. Then, the dried product is calcined in a helium inert gas atmosphere for 2-10 hours, and the calcination temperature is set to 200-600°C to obtain ZnZrO x / Cu2O materials.

[0013] Optionally, the Cu precursor in step (1) comprises one of the following compounds:

[0014] CuSO4, CuCl2·2H2O, Cu(CH3COO)2, Cu(NO3)2·3H2O

[0015] Optionally, the reducing agent in step (1) comprises one of the following compounds:

[0016] Sodium citrate, L-ascorbic acid

[0017] Optionally, in step (2), the Zn 2+ The precursor comprises one of the following compounds:

[0018] Zn(NO3)2·6H2O, Zn(CH3COO)2, Zn(OH)2, Zn2(OH)2CO3

[0019] Optionally, in step (2), the Zr 4+ The precursor comprises one of the following compounds:

[0020] Zr(NO3)4·5H2O, ZrOCl2·8H2O

[0021] Optionally, the ZnZrO added in step (2) xThe mass of the metal precursor is 0.02 to 0.4 times the mass of Cu2O, wherein the molar ratio of Zn to Zr is 1.0 to 5.0.

[0022] Optionally, in step (2), the treatment is carried out in a helium inert gas atmosphere at a temperature of 200 to 600° C. for 1 to 10 hours.

[0023] Optionally, the ultrapure water in steps (1) and (2) can be replaced by deionized water.

[0024] Compared with the existing technology, the solution provided by the embodiment of the present invention can produce the following beneficial effects:

[0025] A Cu2O-loaded ZnZrO x The copper-containing compound was selected as the precursor, sodium citrate was selected as the reducing agent, and sodium hydroxide was used as the precipitating agent to prepare the Cu2O carrier-loaded ZnZrO by liquid phase reduction method. x The inverse structure of the metal oxide. Its active center distribution is relatively uniform, which increases the contact area between the catalyst and the reactant, provides sufficient reactive active sites, and is conducive to improving the hydrogenation activity and methanol selectivity. At the same time, the preparation process and method of the present invention are simple and feasible, low cost, mild conditions, good reproducibility, and strong controllability. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is a SEM image of Cu2O prepared in Example 1;

[0027] Figure 2 is the XRD pattern of Cu2O prepared in Example 1;

[0028] Figure 3 The surface of Cu2O prepared in Example 1 is loaded with ZnZrO x XRD pattern of

[0029] Figure 4 The surface of Cu2O prepared in Example 1 is loaded with ZnZrO x The Cu surface loaded with ZnZrO prepared in Comparative Example 1 x CO2 conversion performance diagram;

[0030] Figure 5 The surface of Cu2O prepared in Example 1 is loaded with ZnZrO x The Cu surface loaded with ZnZrO prepared in Comparative Example 1 x Methanol selectivity performance diagram. DETAILED DESCRIPTION

[0031] The embodiment of the present invention provides a Cu2O loaded ZnZrO x The composite metal oxide reverse phase catalyst is applied to CO2 hydrogenation to produce methanol, and is characterized by comprising: a Cu2O carrier and ZnZrO x Oxide reverse catalyst, x is 1-3.

[0032] Wherein, the powder size of the Cu2O carrier is (10-2000) nm, and the ZnZrO x The powder size of the oxide is (1 to 100) nm.

[0033] The embodiment of the present invention provides a Cu2O loaded ZnZrO x The preparation method of the composite metal oxide reverse phase catalyst is characterized in that a fixed bed reactor is used, a mixed gas with a molar ratio of CO2 / H2 / N2=1 / 1.0~5.0 / 0.5~5 is introduced, the flow rate is controlled at 10~150mL / min, the reaction pressure is maintained at 0.5~5MPa, the reaction temperature is set at 180~300℃, and a gas chromatograph is used for online detection and calculation to obtain the CO2 conversion rate and methanol selectivity. The preparation method specifically comprises the following steps:

[0034] (1) Contains Cu 2+ The precursor, the reducing agent, the 4.8M NaOH solution and the ultrapure water are mixed uniformly in a mass ratio of 1-15:10-25:10-25:500-2500, the reaction temperature is set to 50-150°C, and the reaction is stirred at a speed of 100-1000 rpm for 0.5-25 hours. Subsequently, 0.1-15g of ascorbic acid is added, and the reaction is stirred at a speed of 100-1000 rpm for 0.5-30 hours. After the product is cooled to room temperature, it is alternately washed with ultrapure water and anhydrous ethanol and centrifuged. It is dried in a vacuum drying oven at 40-100°C for 6-72 hours to obtain the Cu2O material.

[0035] (2) Cu2O and Zn obtained in step (1) above 2+ Precursor, Zr 4+ The precursor and ultrapure water are mixed evenly in a mass ratio of 1.5-15:0.1-3:0.1-5:1.5-15, the reaction temperature is set to 50-250°C, and the reaction is stirred at a speed of 100-1000 rpm for 0.5-30 hours. Dry in a vacuum drying oven at 40-100°C for 6-72 hours. Then, the dried product is calcined in a helium inert gas atmosphere for 2-10 hours, and the calcination temperature is set to 200-600°C to obtain ZnZrO x / Cu2O materials.

[0036] Optionally, the Cu precursor in step (1) comprises one of the following compounds:

[0037] CuSO4, CuCl2·2H2O, Cu(CH3COO)2, Cu(NO3)2·3H2O

[0038] Optionally, the reducing agent in step (1) comprises one of the following compounds:

[0039] Sodium citrate, L-ascorbic acid

[0040] Optionally, in step (2), the Zn 2+ The precursor comprises one of the following compounds:

[0041] Zn(NO3)2·6H2O, Zn(CH3COO)2, Zn(OH)2, Zn2(OH)2CO3

[0042] Optionally, in step (2), the Zr 4+ The precursor comprises one of the following compounds:

[0043] Zr(NO3)4·5H2O, ZrOCl2·8H2O

[0044] Optionally, the ZnZrO added in step (2) x The mass of the metal precursor is 0.02 to 0.4 times the mass of Cu2O, wherein the molar ratio of Zn to Zr is 1.0 to 5.0.

[0045] Optionally, in step (2), the helium inert gas treatment is carried out at a temperature of 200 to 600° C. for 1 to 10 hours.

[0046] Optionally, the ultrapure water in steps (1) and (2) can be replaced by deionized water.

[0047] The following is a detailed description of Cu2O loading ZnZrO with several specific examples. x The structure and preparation process of the composite metal oxide reverse catalyst.

[0048] Example 1: Preparation of Cu2O loaded ZnZrO x The reverse catalyst structure

[0049] 0.80g sodium citrate and 100mL ultrapure water were added to a round-bottom flask and mixed evenly. The mixture was heated in a 90℃ water bath for 20min. Then 1ml of 1.2M CuSO4 solution was injected with a pipette. After 30min, 1mL of 4.8M NaOH solution was injected into the solution. Then 1mL of 1.2M ascorbic acid (AA) was injected and kept in a water bath for 30min. Filtered and washed three times with deionized water and alcohol. After drying in a vacuum oven at 60℃ for 2h, a Cu2O material with a size of 800nm ​​was obtained.

[0050] The Cu2O obtained above and ultrapure water were mixed evenly in a mass ratio of 1:2, and 0.2g of Zn(NO3)2·6H2O and 0.1314g of Zr(NO3)4·5H2O were added and impregnated for 12h. The mixture was dried in a vacuum oven at 200℃ for 24h. The dried product was then calcined in a helium inert gas atmosphere for 5h to obtain ZnZrO x / Cu2O materials, among which ZnZrO x The material size is 50nm.

[0051] Comparative Example 1: Preparation of Metal Cu Support Loaded ZnZrO x structure

[0052] A sufficient amount of Cu2O synthesized in the example was weighed and placed in a magnetic boat, and calcined in a tube furnace at 400°C in a 10% H2 / Ar mixed gas atmosphere for 4 hours, with the heating rate controlled at 5°C / min. After cooling to room temperature, a metal Cu carrier material with a size of 800 nm was obtained.

[0053] Weigh 1g of Cu carrier and ultrasonically disperse it in 2mL of ultrapure water, add 0.0916g of Zn(NO3)2·6H2O and 0.1314g of Zr(NO3)4·5H2O, impregnate and stir for 10h until the ultrapure water is completely evaporated, and place it in an oven to dry for 6h. Then, the sample is calcined at 400℃ in a helium inert gas atmosphere for 4h, and the heating rate is controlled at 5℃ / min to obtain Cu carrier loaded ZnZrO x Materials (ZnZrO x / Cu), of which ZnZrO x The material size is 50nm.

[0054] By loading ZnZrO on the Cu2O surface obtained in Example 1 x And the metal Cu surface loaded with ZnZrO obtained in Comparative Example 1 xThe sample was subjected to CO2 hydrogenation catalytic reaction. A fixed bed reactor was used to introduce a mixed gas with a molar ratio of CO2 / H2 / N2 = 1.0 / 1.0 / 5.0. The flow rate was controlled at 100 mL / min, the reaction pressure was maintained at 3 MPa, the reaction temperature was set at 250 ° C, and the gas chromatograph was used to detect and calculate the CO2 conversion rate and methanol selectivity online. The prepared Cu2O surface loaded with ZnZrO x The sample is loaded with ZnZrO on the surface of metal Cu. x The CO2 hydrogenation catalytic performance of the sample was significantly improved. The CO2 conversion rate was as high as 28.88% at 300°C, which was higher than that of ZnZrO loaded on the surface of metal Cu. x (15.24%). At the same time, the surface of Cu2O prepared at 300℃ loaded with ZnZrO x The methanol selectivity of the sample is as high as 45.13%, which is higher than that of the ZnZrO x The sample is 15% higher. This indicates that the Cu2O surface is loaded with ZnZrO x The samples have good CO2 conversion and methanol selectivity.

[0055] Example 2

[0056] Cu2O loaded ZnZrO x The method for preparing a composite metal oxide reverse phase catalyst comprises the following steps:

[0057] 0.40g sodium citrate and 400mL ultrapure water were added to a round-bottom flask and mixed evenly. The mixture was heated in a 20°C water bath for 20 minutes. Then 1ml of 1.2M CuSO4 solution was injected with a pipette. After 5 minutes, 1mL of 4.8M NaOH solution was injected into the solution. Then 1mL of 1.2M ascorbic acid (AA) was injected and kept in a water bath for 30 minutes. The mixture was filtered and washed three times with deionized water and alcohol. After drying in a vacuum oven at 60°C for 2 hours, a Cu2O material with a size of 500nm was obtained.

[0058] The Cu2O obtained above and ultrapure water were mixed evenly in a mass ratio of 1:2, and 0.0916g of Zn(NO3)2·6H2O and 0.1314g of Zr(NO3)4·5H2O were added and impregnated for 12h. The mixture was dried in a vacuum oven at 200℃ for 24h. The dried product was then calcined in a helium inert gas atmosphere for 5h to obtain ZnZrO x / Cu2O materials, among which ZnZrO x The material size is 50nm.

[0059] The ZnZrO in Example 4 was subjected to CO2 hydrogenation reaction. x / Cu2O material was placed in a fixed bed reactor, and a mixed gas with a molar ratio of CO2 / H2 / N2 = 1.0 / 1.0 / 5.0 was introduced, the flow rate was controlled at 100mL / min, the reaction pressure was maintained at 3MPa, the reaction temperature was set at 250°C, and the CO2 conversion rate and methanol selectivity were obtained by online detection and calculation using a gas chromatograph. At 300°C, the CO2 conversion rate reached 23.67% and the methanol selectivity reached 42.67%.

[0060] Example 3

[0061] Cu2O loaded ZnZrO x The method for preparing a composite metal oxide reverse phase catalyst comprises the following steps:

[0062] 0.20g sodium citrate and 400mL ultrapure water were added to a round-bottom flask and mixed evenly. The mixture was heated in a 20℃ water bath for 20min. Then 1ml of 1.2M CuSO4 solution was injected with a pipette. After 5min, 1mL of 4.8M NaOH solution was injected into the solution. Then 1mL of 1.2M ascorbic acid (AA) was injected and kept in a water bath for 30min. The mixture was filtered and washed three times with deionized water and alcohol. After drying in a vacuum oven at 60℃ for 2h, a Cu2O material with a size of 100nm was obtained.

[0063] The Cu2O obtained above and ultrapure water were mixed evenly in a mass ratio of 1:2, and 0.0916g of Zn(NO3)2·6H2O and 0.1314g of Zr(NO3)4·5H2O were added and impregnated for 12h. The product was placed in a vacuum drying oven, the reaction temperature was set to 200℃, and dried for 24h. The dried product was then calcined in a helium inert gas atmosphere for 5h to obtain ZnZrO x / Cu2O materials, among which ZnZrO x The material size is 50nm.

[0064] The ZnZrO in Example 3 was subjected to CO2 hydrogenation reaction. x / Cu2O material was placed in a fixed bed reactor, and a mixed gas with a molar ratio of CO2 / H2 / N2 = 1.0 / 1.0 / 5.0 was introduced, the flow rate was controlled at 100mL / min, the reaction pressure was maintained at 3MPa, the reaction temperature was set at 250°C, and the CO2 conversion rate and methanol selectivity were obtained by online detection and calculation using a gas chromatograph. At 300°C, the CO2 conversion rate reached 19.12% and the methanol selectivity reached 40.67%.

[0065] Example 4

[0066] Cu2O loaded ZnZrO xThe method for preparing a composite metal oxide reverse phase catalyst comprises the following steps:

[0067] 0.05g sodium citrate and 400mL ultrapure water were added to a round-bottom flask and mixed evenly. The mixture was heated in a 20°C water bath for 20 minutes. Then 1ml of 1.2M CuSO4 solution was injected with a pipette. After 5 minutes, 1mL of 4.8M NaOH solution was injected into the solution. Then 1mL of 1.2M ascorbic acid (AA) was injected and kept in a water bath for 30 minutes. The mixture was filtered and washed three times with deionized water and alcohol. After drying in a vacuum oven at 60°C for 2 hours, a Cu2O material with a size of 50nm was obtained.

[0068] The Cu2O obtained above and ultrapure water were mixed evenly in a mass ratio of 1:2, and 0.0916g of Zn(NO3)2·6H2O and 0.1314g of Zr(NO3)4·5H2O were added and impregnated for 12h. The mixture was dried in a vacuum oven at 200℃ for 24h. The dried product was then calcined in a helium inert gas atmosphere for 5h to obtain ZnZrO x / Cu2O materials, among which ZnZrO x The material size is 50nm.

[0069] The ZnZrO in Example 4 was subjected to CO2 hydrogenation reaction. x / Cu2O material was placed in a fixed bed reactor, and a mixed gas with a molar ratio of CO2 / H2 / N2 = 1.0 / 1.0 / 5.0 was introduced, the flow rate was controlled at 100mL / min, the reaction pressure was maintained at 3MPa, the reaction temperature was set at 250°C, and the CO2 conversion rate and methanol selectivity were obtained by online detection and calculation using a gas chromatograph. At 300°C, the CO2 conversion rate reached 17.54% and the methanol selectivity reached 38.12%.

Claims

1. A Cu2O-loaded ZnZrO x The composite metal oxide reverse phase catalyst is characterized in that: include: Containing Cu2O support and ZnZrO x Oxide reverse catalyst, x is 1-3.

2. Cu2O loaded ZnZrO according to claim 1 x The composite metal oxide reverse phase catalyst is characterized in that: The powder size of Cu2O carrier is 10~2000nm, ZnZrO x The powder size of the oxide is 1 to 100 nm.

3. A method for preparing a reverse phase catalyst as claimed in claim 1 or 2, characterized in that: The preparation method specifically comprises the following steps: (1) Contains Cu 2+ The precursor, the reducing agent, the 4.8M NaOH solution and the ultrapure water are uniformly mixed in a mass ratio of 1-15:10-25:10-25:500-2500, the reaction temperature is set to 50-150°C, and the reaction is stirred at a speed of 100-1000 rpm for 0.5-25 hours; then 0.1-15g of ascorbic acid is added, and the reaction is stirred at a speed of 100-1000 rpm for 0.5-30 hours; after the product is cooled to room temperature, it is alternately washed with ultrapure water and anhydrous ethanol and centrifuged; and dried in a vacuum drying oven at 40-100°C for 6-72 hours to obtain a Cu2O material; (2) Cu2O and Zn obtained in step (1) above 2+ Precursor, Zr 4+ The precursor and ultrapure water are mixed uniformly in a mass ratio of 1.5-15:0.1-3:0.1-5:1.5-15, the reaction temperature is set to 50-250°C, and the reaction is stirred at a speed of 100-1000 rpm for 0.5-30 hours; the product is dried in a vacuum drying oven at 40-100°C for 6-72 hours; and the dried product is then calcined in a helium inert gas atmosphere for 2-10 hours, and the calcination temperature is set to 200-600°C to obtain ZnZrO x / Cu2O materials.

4. The method according to claim 3, characterized in that Step (1) contains Cu 2+ The precursor is one of the following compounds: CuSO4, CuCl2·2H2O, Cu(CH3COO)2, Cu(NO3)2·3H2O.

5. The method according to claim 3, characterized in that: The reducing agent in step (1) comprises one of the following compounds: sodium citrate and L-ascorbic acid.

6. The method according to claim 3, characterized in that Step (2) Zn 2+ The precursor comprises one of the following compounds: Zn(NO3)2·6H2O, Zn(CH3COO)2, Zn(OH)2, Zn2(OH)2CO3.

7. The method according to claim 3, characterized in that Step (2) Zr 4+ The precursor comprises one of the following compounds: Zr(NO3)4·5H2O, ZrOCl2·8H2O.

8. The preparation method according to claim 3, characterized in that: The Zn added in step (2) 2+ Precursor and Zr 4+ The sum of the masses of the precursors is 0.02 to 0.4 times the mass of Cu2O, wherein the molar ratio of Zn to Zr is 1.0 to 5.

0.

9. The method according to claim 3, characterized in that: The ultrapure water in steps (1) and (2) can be replaced with deionized water.

10. The use of the reverse phase catalyst according to claim 1 or 2, characterized in that: A fixed bed reactor is used, and a mixed gas with a molar ratio of CO2 / H2 / N2=1 / 1.0~5.0 / 0.5~5 is introduced, the flow rate is controlled at 10~150mL / min, the reaction pressure is maintained at 0.5~5MPa, and the reaction temperature is set at 180~300℃.

Citation Information

Patent Citations

  • Method for catalytically preparing fatty alcohol

    CN105777488A

  • ZnZrOx solid solution catalyst for synthesizing methanol through hydrogenation of carbon dioxide, and preparation method and application of ZnZrOx solid solution catalyst

    CN109420486A

  • Cu2O loaded ZnO catalyst for electrochemical reduction of CO2

    CN112642434A

  • Reverse-phase metal oxide catalyst for preparing methanol through carbon dioxide hydrogenation

    CN118045595A

  • Zn-ce02-zro2 catalyst for hydrogen production via methanol partial oxidation

    US20180185823A1

Cited By

  • A CeZrO x / Cu2O / Cu core-shell reverse phase catalyst, preparation method and application thereof

    CN122850172A